ANALISIS PEMANFAATAN MEDIA DIGITAL DALAM MENGATASI KEJENUHAN BELAJAR IPAS DI SEKOLAH DASAR - Huda, Ida Nurul; Alfira, Ajeng; Setiawati, Tia; Farhurohman, Oman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the use of digital media in overcoming learning boredom in IPAS at the elementary school level. Learning boredom is often caused by monotonous teaching methods, limited learning media, and low student engagement. This research uses a literature review method by examining relevant studies published between 2020 and 2025. The results show that digital media such as learning videos, animations, interactive applications, and educational games can create a more engaging and interactive learning environment. These media help increase students’ motivation, participation, and understanding of abstract concepts through visual and audiovisual presentations. However, the implementation of digital media still faces challenges, including limited teacher competence, inadequate facilities, and low digital literacy among students. Therefore, efforts such as teacher training, improving infrastructure, and collaboration between schools and parents are needed. In conclusion, digital media play an important role in reducing learning boredom and improving the quality of IPAS learning in elementary schools.